Authors' response to "Multiple-job holding is not a type of precarious employment" - Isa Koranyi; Johanna Jonsson; Torkel Rönnblad; Leo Stockfelt; Theo Bodin (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
We would like to thank the authors of the letter entitled "Multiple job holding is not a type of precarious employment" (1) and extend our thanks to the Editor-in-Chief for giving us the opportunity to respond. The authors of the letter point out that precarious employment is a multidimensional construct, with which we completely agree. There is however no consensus on which dimensions should be included in this construct, and therefore we chose a broad approach including three of the most wide-spread definitions: Guy Standing's (2), the Employment Precarious Scale (3) and the ILO`s (4). A one-on-one comparison of these can be found in table 1 of our review (5). We found very few studies using a multidimensional definition of precarious employment and so our review ended up investigating studies on single dimensions, such as holding multiple jobs. The main argument of Bouwhuis et al is that multiple job holding should not be included as a dimension of precarious employment as it "does not relate to the quality of the terms of employment" and "not all multiple job holders are vulnerable or precarious". This argument could be made about any single dimension and is the rational behind creating a multidimensional construct, ie, no single variable is enough to capture the complexity of the issue. In the case of employment instability, some temporary workers are precarious and some are not (6). Some part-time workers are precarious although many are not. And as the authors of the letter has shown in their own study; some multiple job holders are precarious while some are not (7). Thus, we can all agree that holding multiple jobs is not the same as being precariously employed. However, we believe that multiple job holding should continue to be considered as an important dimension of precarious employment. There are several ongoing initiatives to try to reach consensus on what comprises precarious employment. We are glad that the debate on precarious employment is alive and well in this journal and elsewhere. Any reader interested in contributing to this effort are welcome to contact us. References 1. Bouwhuis S, Geuskens GA, van der Beek AJ, Boot CRL. Multiple-job holding is not a type of precarious employment. Scand J Work Environ Health - online first. https://doi.org/10.5271/sjweh.3782 2. Standing G. The precariat: The new dangerous class. London: Bloomsbury Publishing; 2011. 3. Vives A, Amable M, Ferrer M, , Moncada S, Llorens C, Muntaner C, et al. The Employment Precariousness Scale (EPRES): psychometric properties of a new tool for epidemiological studies among waged and salaried workers. Occup Environ Med. 2010;67(8):548-55. https://doi.org/10.1136/oem.2009.048967. 4. ILO. Non-standard forms of employment. Geneva: International Labour Office; 2015. 5. Koranyi I, Jonsson J, Ronnblad T, Stockfelt L, Bodin T.. Precarious employment and occupational accidents and injuries - a systematic review. Scand J Work Environ Health. 2018;44(4):341-50. https://doi.org/10.5271/sjweh.3720. 6. Julià M, Vives A, Tarafa G, Benach J. S09-4 The precarization of the spanish labour market and its impact on mental health. Occup Environ Med. 2016;73:A109-A110 https://doi.org/10.1136/oemed-2016-103951.296. 7. Bouwhuis S, Hoekstra T, Bongers PM, Boot CRL, Geuskens GA, van der Beek AJ. Distinguishing groups and exploring health differences among multiple job holders aged 45 years and older. Int Arch Occup Environ Health. 2018:1-13. https://doi.org/10.1007/s00420-018-1351-2.